Tanggung jawab Pemberitaan Pers dalam Perspektif Keadilan dan Hak Asasi Manusia di Indonesia - Samsul Wahidin (Fakultas Hukum Universitas Islam Indonesia, 2000)
Responsibility on press presentation is printed media has been unclear. Responsibility mechanism with